(untitled) (Medico Legal Update, 2021)
Background: Psoriasis is a skin disease that was associated with metabolic and clinical changes which suggest that psoriasis is a systemic rather than local disease. Aim: To illustrate whether psoriasis is local or systemic disease through analysis of some biomarkers. Materials and Method: A 256 subjects with psoriasis and 221 sex and age matched controls were included in the study. Serum total cholesterol [TC], high density lipoprotein [HDL], Malondialdehyde [MDA], triglycerides [TG], and total antioxidant capacity [TCA] were determined using commercial kits. Results: There were no significant differences between psoriasis and control groups in regards to mean age and gender distribution, however, there was a significant difference [p<0.01] in BMI. Additionally, TC, TG, LDL and NHDL were significantly higher [P<0.001] in patients with psoriasis than in controls, while HDL was significantly lower in psoriasis than in controls. MDA mean serum level was significantly higher [P<0.001] lower while TCA value was significantly [P<0.001] lower in subjects with psoriasis as compared controls. Lipid profile rates and oxidation index were significantly higher in psoriasis than in controls, while the anti-oxidation index was significantly lower in psoriasis. Conclusion: These study findings suggest that psoriasis may be a systemic disease rather than local skin disease.